ANALISIS PENGARUH ABSTENTION (GOLONGAN PUTIH) PADA PILKADA KOTA DEPOK TAHUN 2020 - Andini Ela Prasetya, (2023)
In several election activities, abstentions often exceed the number of votes from the winning pair. This phenomenon had occurred in the Regional Head Election (pilkada) in Depok, West Java in 2020. In that year, the total number of voters in Depok was 1,229,362 people, but the number of voters was only 777,737 (63%). There were 451,625 (37%) Depok residents who either abstained or did not come to the TPS. This of course can become a problem if it occurs repeatedly and must be a problem that election actors will immediately address. This study aims to discuss the factors that became the reasons for voters in Depok City to abstain from the Depok City election activities. The research method used is the Mixed Method with the Embedded Mixed Method model, which is conducting surveys and interviews at the same time. The sampling technique used proportionate sampling and snowball sampling. The quantitative data testing is done by testing the data in the form of validity and reliability tests, then normality tests using the Kolomogorov-Smirnov, and hypothesis testing using Chi Square or kai squared. This study found that the biggest factor that became the reason for the abstentions of the people of Depok was the factor of political attitudes, namely their consistency in choosing parties in general election activities and the adequacy of information obtained by respondents regarding election activities. The second reason is regarding the economic system in the form of jobs, income, receiving assistance, and the needs needed by the respondents. The third reason is because of the social attachment factor, namely the influence between the organization or the people closest to the respondent which influences the respondent to abstain. The fourth reason is Demographic factors where individual identity influences respondents to abstain. The reason with the smallest effect is the COVID-19 factor regarding the opinion of respondents to regional election activities during a pandemic and respondents who have been infected with the COVID-19 virus.